Pengaruh Konsentrasi Amonium Peroksidisulfat Sebagai Oksidator Pada Sintesis Polianilin Ter-doping HCl - Srikandi, Nona
Polyaniline (PANI) is a conductive polimer which commonly applied in solar cells, gas censors, capacitors, and batteries. Polyaniline was investigated intensively due to its high conductivity, good thermal stability, unique doping mechanism and ease to synthesize. Conductivity and morphology of polyaniline depend on the type of solvent, oxidizers, monomer, synthesis method, temperature and dopant. HCl-doped polyaniline was synthesized by means of chemical oxydation of aniline using ammonium peroxydisulphate (APS) as oxidizer in HCl solution at -20 °C. The influences of oxidizer concentration (0,1-1 M APS) on structure, electrical conductivity, and morphology were investigated. The characterization using Electrochemical Impedance Spectroscopy (EIS) shows that conductivity of PANI decreases with the increase of APS concentration. However, conductivity of PANI reached its maximum of 0,3622 S cm-1 when polymerized using 0,5 M APS. Fourier Transformed Infrared (FTIR) and Raman Spectroscopy measurement indicates that conducting state of PANI, Emeraldine Salt (ES), had been synthesized, except for 1 M APS which yielded PANI in its fully-oxidized state, Pernigraniline Salt (PS). Sample morphology was characterized using Scanning Electron Microscope (SEM). Nanorod PANI with diameter around 80-110 nm was observed, except for PANI with 1 M APS which formed granular particles. PANI with 0,5 M APS provided the largest nanorod size. XRD characterization showed that average grain size was almost similar, leaving out the 1 M PANI with the smallest size. Diffuse reflectance characterization shows that entire synthesized PANI has direct allowed transition. The characterisations shows there are optimum conditions for oxidizer concentration on HCl doped PANI synthesis based on their electrical conductivity.